Mental Health Among Adolescents Exposed to a Tornado: The Influence of Social Support and Its Interactions With Sociodemographic Characteristics and Disaster Exposure. Issue 3 (29th May 2015) - Paul, Lisa A.; Felton, Julia W.; Adams, Zachary W.; Welsh, Kyleen; Miller, Stephanie; Ruggiero, Kenneth J.
Abstract: Approximately 25% of youths experience a natural disaster and many experience disaster‐related distress, including symptoms of posttraumatic stress disorder (PTSD) and depression. This study contributes to the literature by examining PTSD and depressive symptoms among 2, 000 adolescents (50.9% female, 70.5% White) assessed after exposure to tornadoes in 2011. The authors hypothesized that greater tornado exposure, female sex, and younger age would be associated with distress, and that social support would interact with these associations. Analyses showed that PTSD symptoms were associated with lower levels of social support (β = −.28, p < .001), greater tornado exposure (β = .14, p < .001), lower household income (β = −.06, p = .013, female sex (β = −.10, p < .001), and older age (β = .07, p = .002), with a 3‐way interaction between tornado exposure, sex, and social support (β = −.06, p = .017). For boys, the influence of tornado exposure on PTSD symptoms increased as social support decreased. Regardless of level of tornado exposure, low social support was related to PTSD symptoms for girls; depressive symptom results were similar. These findings were generally consistent with the literature and provide guidance for intervention development focused on strengthening social support at the individual, family, and community levels.